2008
DOI: 10.1590/s0034-71672008000200009
|View full text |Cite
|
Sign up to set email alerts
|

Medicina popular: benefícios e malefícios das plantas medicinais

Abstract: Descriptive study which aims to verify if the herbalist offer the information correct for the use of the medicinal plants; if they give for the customers concerning the possible poisonings or interaction with the allopathic guide and also if there is a criteria for the commercialization of the phytotherapics. A questionnaire was used containing open and closed questions involving aspects of the performance of the herbalists with the phytotherapics. The herbalists know the majority of the medicinal plants, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
82

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 10 publications
2
14
0
82
Order By: Relevance
“…França, Souza and Baptista, as a misconception, point out the lack of toxicity of the plants because there are variety of medicinal plants, and the benefits that can be generated with its consumption can cause toxicity by the presence of pharmacologically active and toxic constituents, which can cause health risks. 18 Some ACS reported that there are plants harmful to the health of pregnant women, causing miscarriage. Rodrigues and colleagues report that many plants used in daily life have aggressive substances, providing toxicological risks.…”
Section: Discussionmentioning
confidence: 99%
“…França, Souza and Baptista, as a misconception, point out the lack of toxicity of the plants because there are variety of medicinal plants, and the benefits that can be generated with its consumption can cause toxicity by the presence of pharmacologically active and toxic constituents, which can cause health risks. 18 Some ACS reported that there are plants harmful to the health of pregnant women, causing miscarriage. Rodrigues and colleagues report that many plants used in daily life have aggressive substances, providing toxicological risks.…”
Section: Discussionmentioning
confidence: 99%
“…Todavia, o uso deve ser precedido por criteriosa identificação e classificação botânica a fim de evitar a indução de erros e problemas durante a utilização. Muitas vezes os profissionais de saúde associam o uso destes medicamentos com os medicamentos alopáticos França et al, (2008), o que pode gerar riscos, uma vez que diversas interações têm sido descritas entre fitoterápicos e fármacos quimicamente definidos, algumas associadas à modulação da atividade enzimática no sítio de atuação (FRANCO, 2003).…”
Section: Figura 11 -Frequência Do Atendimento a Pacientes Com Problemunclassified
“…Faveleira has several uses, including recovery of degraded areas, human and animal (goats, cattle, and sheep) feed, medicinal, wood, and fuel (Arriel et al, 2004;França et al, 2008;Pordeus Neto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%